2022
DOI: 10.1136/bmjopen-2021-056640
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural perspectives on suicidal behaviour at the Coast Region of Kenya: an exploratory qualitative study

Abstract: ObjectivesTo explore perceived sociocultural factors that may influence suicidality from key informants residing in coastal Kenya.DesignWe used an exploratory qualitative study design.SettingMombasa and Kilifi Counties of Coastal Kenya.Participants25 key informants including community leaders, professionals and community members directly and indirectly affected by suicidality.MethodsWe conducted in-depth interviews with purposively selected key informants to collect data on sociocultural perspectives of suicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…They documented that the stigma was mainly driven by the dilapidated and neglected state of these facilities, as well as the lack of medication and affordable counselling services. 27 Often, because of the belief that suicidal behaviour may be linked to supernatural elements such as witchcraft or curses, 12 some people are more likely to seek mental health-related support from traditional and faith healers. 28 These services are arguably less effective or potentially harmful if the healer lacks a good understanding of mental health problems and when to refer severe cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They documented that the stigma was mainly driven by the dilapidated and neglected state of these facilities, as well as the lack of medication and affordable counselling services. 27 Often, because of the belief that suicidal behaviour may be linked to supernatural elements such as witchcraft or curses, 12 some people are more likely to seek mental health-related support from traditional and faith healers. 28 These services are arguably less effective or potentially harmful if the healer lacks a good understanding of mental health problems and when to refer severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…The first paper explored how suicidal behaviour is conceptualised in this region, with a focus on sociocultural factors influencing suicidality. 12 It showed that suicide is conceptualised as a supernatural phenomenon in this area, perceptions around suicidality differed by gender and age, and suicidal behaviour remains highly stigmatised, leading to a convoluted self-harm care pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies in Kenya have examined risk factors for suicidal behaviour. Many of these studies have been quantitative surveys thereby lacking explanations and an in-depth understanding behind these factors (4,5). Some suicide risk factors repeatedly highlighted in these quantitative studies include having a mental health condition and primarily depression and substance use disorders (5).…”
Section: Introductionmentioning
confidence: 99%